External Debt and Growth Dynamics - CHEN, Si (Institutional Knowledge at Singapore Management University, 2006)
Based on an extended growth model, this thesis further explores the joint dynamics between external debt and growth. The model explicitly expresses this growth dynamic mechanism incorporating external debt as an important explanatory variable with risk premium and other related structural factors. The interactions between external debt and growth are interpreted as directly and mainly through the channel of capital accumulation and indirectly through technology change. These constitute the functional form foundation to solve the main concern on the effect of external debt upon growth adjustment path. The numerical simulations of the model indicate that when external debt is assumed to be exogenous, the adjustment speed rises with higher risk premium or debt level. However, when external debt is assumed to be endogenous, the adjustment speed turns out to be lower with higher risk premium when external debt goes beyond a certain level. In comparison with the numerical simulations based on the extended model and specified parameter values, this study also contains a nonparametric empirical approach that focuses on the debt-growth relation in the context of the Philippine economy. Relaxing the structure functional form and assumptions, the nonparametric estimation uses the simplified form linking the change of growth rate with lagged external debt level. The results report that the effect of external debt on growth in Philippines is not very significant; while, GDP and export growth beyond some certain level are accompanied by external debt decreases. Simultaneity and omitted variables in the nonparametric model may bias these results---hence these results should be considered as initial steps in the direction for testing the real debt-growth relation.